Case Report: An Adolescent Soft Tissue Sarcoma With YWHAE-NUTM2B Fusion Is Effectively Treated With Combined Therapy of Epirubicin and Anlotinib - He, Jiajia; Xu, Yanjie; Ni, Xuefeng; Zhang, Dachuan; Zhao, Jiemin (Frontiers in Oncology, 2022)
Soft tissue sarcoma is a relatively rare entity that comprises heterogeneous types of tumors. Here we report the case of a 14-year-old girl of pelvic sarcoma with an YWHAE-NUTM2B fusion gene. This fusion transcript has been reported in endometrial stromal sarcomas and clear cells renal sarcomas but its description in pelvic sarcomas is recent. To our knowledge, this is the first case report describing this translocation in an adolescent patient with soft tissues sarcoma. The patient underwent cytoreductive surgery, followed by systemic chemotherapy and targeted drug treatment. Surprisingly, the treatment was effective, and the young patient being follow-up with our department.